Kajian Gaya Bahasa dan Pesan Moral Pada Teks Lagu dalam Album Untukmu Selamanya Karya Ungu Band - Septiani Lestari; Teguh Suharto; Panji Kuncoro Hadi (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
Humans are very close to the song. Songs often appear in mass media such as television, radio, and the internet. Song is a form of means of communication in the form of audio. Through a song a message can be conveyed in a different way, namely with music. Music is a work of art. Art is very attached to human civilization which moves with the development of culture, technology, and science. Songs can be a means of communication for someone and the audience, because that is one of the goals of the song to convey the message and feelings of the singer, this message can be conveyed through the moral message contained. In addition to the moral message in the song, there is a unique language used by the songwriter. The science of studying language in songs popularized by Ungu uses stylistic studies. Stylistics is the study of style or style of language. This study aims to describe the use of language style and moral messages contained in the album For You Slamanya by Ungu band.The stages of data collection researchers are by (1) identifying words, phrases, and sentences, how to identify includes style of language and moral messages. (2) record identified data on another sheet to distinguish pure data from data that has been sorted according to categorization. How to analyze data in the following ways: (1) data collection stage; (2) data reduction stage; (3) data selection stage; (4) conclusionThe results of the analysis conducted by the researcher through 12 Ungu band song texts with the album title For You Selamnya found 1 simile, 6 metaphorical figurative language, 8 epic simile figurative language, 7 personification figurative language, and 2 figurative language. synecdoche language, so that a total of 24 figurative language.While the moral messages found as many as 20 data. The moral message of human relations with God found 1 data, the moral message of human relations with other human beings found 7 data, and the human relationship with himself found 12 data.